Revitalization of BUMDes Ngudi Sejahtera Ngunut to Increase Village Economic Independence - Novitasari, Rika; Harsanti, Tikka Dessy (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to examine the revitalization of BUMDes Ngudi Sejahtera in Ngunut Village, Ngunut District, Tulungagung Regency, East Java Province. This research uses a sociological approach and empirical juridical research methods. While secondary data was collected through literature reviews and observations, primary data was collected through interviews and analysis using sociological juridical analysis with stages of data display, data reduction and drawing conclusions. The problem that arises currently is that BUMDes have an important role in exploring, collecting and monitoring village potential, so revitalization initiatives are needed. A professional BUMDes governance structure can contribute to initiatives aimed at improving the local economy as part of local village potential. The aim of revitalizing BUMDes is to increase the role of the organization as a forum for assessing the potential of nearby villages and also to increase the economic independence of the village.